The Effectiveness of Autogenic Relaxation on Sleep Quality and Fatigue Levels in Cancer Patients Undergoing Chemotherapy - Uni Afriyanti; Muhammad Ra’uf; Candra Kusuma Negara; Ricky Prawira (Indonesian Journal of Global Health Research, 2025)
Fatigue and sleep disturbances are two common symptoms experienced by cancer patients undergoing chemotherapy. These conditions negatively impact quality of life and the effectiveness of treatment. One promising non-pharmacological approach is autogenic relaxation, a relaxation technique that combines self-suggestion, controlled breathing, and focused attention on bodily sensations to achieve physical and mental calmness. This study aims to evaluate the effectiveness of autogenic relaxation in improving sleep quality and reducing fatigue levels in cancer patients undergoing chemotherapy. The study employed a quasi-experimental design with a pretest–posttest and control group. A total of 30 patients were divided into two groups: intervention (n = 15) and control (n = 15). The sampling technique used was purposive sampling. The intervention was conducted for two weeks, twice a day, using an audio guide. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI), and fatigue was assessed using the Fatigue Assessment Scale (FAS). The intervention group showed a decrease in mean PSQI scores from 11.2 to 8.1 (p = 0.017) and FAS scores from 34.5 to 28.3 (p = 0.031). Data analysis was performed using the Shapiro–Wilk normality test, followed by the Wilcoxon test for analysis within groups, and the Mann–Whitney test for between groups. The control group did not show any significant changes. These results indicate that autogenic relaxation stimulates a physiological relaxation response that contributes to improved sleep and reduced fatigue. Autogenic relaxation is an effective and applicable non-pharmacological supportive intervention for cancer patients during chemotherapy.